ASSESSMENT OF WORKPLACE DIVERSITY ADOPTION IN ACADEMIC STAFF RECRUITMENT BY THE ENUGU STATE UNIVERSITY OF SCIENCE AND TECHNOLOGY ENUGU, ENUGU STATE - Nwobia, Charles Emeka; Okolie, Jonathan Ibekwe; Oluka, Kingsley Ugochukwu (International Journal of Management and Allied Research (IJMAR), 2023)
The focus of the study was on workplace diversity is implemented in the recruitment process for academic staff at Enugu State University of Science and Technology, Enugu. The specific objectives were included to: evaluate the level of ethnic diversity in the recruitment of academic staff, examine the degree of gender diversity in the recruitment of academic staff and assess the extent of religious diversity in the recruitment of academic staff. A survey approach was adopted. Sample size was determined using Freund and Williams’s formula, resulting in a sample of 462 out of a population of 712. Out of the distributed questionnaires, 366 staff members accurately completed and returned them, resulting in a response rate of 79 percent. Content analysis was employed to assess the validity of the instrument, yielding satisfactory results. The reliability of the instrument was assessed using the Pearson correlation coefficient (r), which indicated a good reliability coefficient of 0.76. For hypothesis testing, the data were analyzed using the Z-test, with the assistance of statistical software, specifically the Special Package for Statistical Software (SPSS). The findings revealed that the adoption of ethnic diversity in the recruitment of academic staff at Enugu State University of Science and Technology is not significantly low (Z(95, n=366) = 4.011 < 5.101, p<.05), gender diversity is not significantly incorporated in the recruitment of academic staff at Enugu State University of Science and Technology, Enugu (Z(95, n=366) = 2.610 < 3.564, p<.05) and the recruitment of academic staff at Enugu State University of Science and Technology demonstrates significant adoption of religious diversity (Z(95, n=366) = 4.353 < 5.233, p<.05). We concluded that workplace diversity, particularly in terms of ethnicity, gender, and religion, significantly influences the recruitment of academic staff at Enugu State University of Science and Technology, Enugu. Embracing a diverse workforce enhances innovation, creativity, and overall performance. The study recommended that Enugu State University of Science and Technology (ESUT) should implement flexible and appropriate strategic planning practices to foster ethnic diversity in the recruitment of academic staff, which will contribute to enhancing the overall performance of the university